2016
DOI: 10.1016/j.nicl.2015.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Transdiagnostic commonalities and differences in resting state functional connectivity of the default mode network in schizophrenia and major depression

Abstract: Schizophrenia and depression are prevalent psychiatric disorders, but their underlying neural bases remains poorly understood. Neuroimaging evidence has pointed towards the relevance of functional connectivity aberrations in default mode network (DMN) hubs, dorso-medial prefrontal cortex and precuneus, in both disorders, but commonalities and differences in resting state functional connectivity of those two regions across disorders has not been formally assessed. Here, we took a transdiagnostic approach to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
57
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 80 publications
6
57
0
Order By: Relevance
“…One expected consequence of DAI in WM is the disruption of neuronal communication among GM areas, which may lead to decreased FC with other brain regions, especially if axonal damage is substantial. For example, reduced FC is consistently found in patients with Alzheimer's disease and schizophrenia, [102][103][104][105][106] wherein structural changes in WM tissue are also found. [107][108][109][110][111][112] Therefore, the DAI model can explain the abnormally decreased FC in the right frontal pole in the present study.…”
Section: Abnormal Decrease In Fc Of the Frontal Pole In Blast Mtbimentioning
confidence: 99%
“…One expected consequence of DAI in WM is the disruption of neuronal communication among GM areas, which may lead to decreased FC with other brain regions, especially if axonal damage is substantial. For example, reduced FC is consistently found in patients with Alzheimer's disease and schizophrenia, [102][103][104][105][106] wherein structural changes in WM tissue are also found. [107][108][109][110][111][112] Therefore, the DAI model can explain the abnormally decreased FC in the right frontal pole in the present study.…”
Section: Abnormal Decrease In Fc Of the Frontal Pole In Blast Mtbimentioning
confidence: 99%
“…Many studies that evaluated resting-state DMN connectivity in schizophrenia using pICA reported on the connectivity between the main DMN hubs and other brain networks (Alonso-Solís et al, 2015; Jafri et al, 2008; Liang et al, 2006; Ongur et al, 2010; Zhou et al, 2007). Of the studies examining DMN connectivity (Alonso-Solís et al, 2015; Chang et al, 2014; Jafri et al, 2008; Li et al, 2015; Liang et al, 2006; Liemburg et al, 2012; Mingoia et al, 2012; Ongur et al, 2010; Schilbach et al, 2016; Zhou et al, 2007), only two studies directly examined connectivity between the DMN hubs (Chang et al, 2014; Liemburg et al, 2012). One of these studies found that individuals with schizophrenia exhibited decreased DMN inter-network connectivity as compared to controls (Liemburg et al, 2012), and one study did not observe group differences in DMN inter-network connectivity (Chang et al, 2014).…”
mentioning
confidence: 99%
“…We postulated that this seemingly contradictory finding may be related to neuropathological features of schizophrenia. Indeed the neuropathological features of depressive symptoms in patients diagnosed with major depressive disorder have been reported to differ from those of depressive symptoms in patients with schizophrenia [69][70][71]. Hence, we posit that ketamine-induced ReHo alterations in schizophrenics may also be different from those in patients with major depressive disorder.…”
Section: Discussionmentioning
confidence: 85%